Reference Group, Gaya Hidup, dan Store Atmosphere sebagai Faktor Pembentuk Budaya Nongkrong Konsumen Angkringan - Levia Inggrit Sayekti; Muhammad Tamim Irsyad; Diah Ayu Novitasari (Commodities, Journal of Economic and Business, 2026)
This study aims to analyze reference groups, lifestyle, and store atmosphere as factors shaping the "hangout culture" among angkringan consumers in Lamongan City. A quantitative, explanatory research approach was employed. Data were collected via questionnaires distributed to 160 angkringan patrons in Lamongan City. Purposive sampling was used for participant selection, and data analysis was conducted using multiple linear regression with SPSS. The results indicate that reference groups, lifestyle, and store atmosphere have a positive and significant influence on consumer hangout culture. Collectively, these three variables also significantly affect hangout culture. An Adjusted R-Square value of 0.544 demonstrates that reference groups, lifestyle, and store atmosphere account for 54.4% of the variation in consumer hangout culture, with the remainder attributed to factors outside the research model. Lifestyle emerged as the most dominant variable in shaping hangout culture. The study's implications highlight the importance of understanding social aspects, lifestyle, and venue atmosphere when designing marketing strategies for *angkringan* businesses, thereby enhancing their appeal as spaces for social interaction and community consumption.